Distribution characteristics of soil crusts under two kinds of aerial seeding plants in the northeastern margin of Tengger Desert - Zhang, Ran; Liang, Yumei; Gao, Yong; Wang, Yanyi (Frontiers in Environmental Science, 2024)
In order to explore the effects of two plants on the spatial distribution and nutrient distribution of crusts in different directions and distances after 30 years of aerial seeding, as well as the relationship between crust thickness and nutrient content, this paper takes the aerial seeding afforestation area in the northeastern margin of Tengger Desert as the research area, and the crusts under the plants of Hedysarum scoparium and Calligonum mongolicum as the research objects. The thickness of the crust of Hedysarum scoparium and Calligonum mongolicum was the largest in the southeast direction and the smallest in the northwest direction. With increasing distance from the plant, it shows a significant decreasing trend. The crust thickness of Hedysarum scoparium was higher than that of Calligonum mongolicum. The nutrient indexes in the southeast direction of the crust of Hedysarum scoparium and Calligonum mongolicum were significantly higher than those in the northwest direction; With the increase of the distance from the root of the plant, the nutrient content showed a significant decreasing trend. The contents of organic matter and available nitrogen in the crust of Calligonum mongolicum were higher than those of Hedysarum scoparium, and the contents of available potassium and available phosphorus were lower than those of Hedysarum scoparium. The trend of nutrient enrichment rate of the crusts of the two plants was consistent with the trend of nutrient distribution. There was a significant positive correlation between the crust thickness and nutrients in the four directions under Calligonum mongolicum. There was a significant positive correlation between the crust thickness and nutrients in the southwest direction under Hedysarum scoparium. The changes of available nitrogen, available phosphorus, available potassium and organic matter content in the crust under Hedysarum scoparium can explain 52.5 % of the change of its thickness. The changes of available nitrogen, available phosphorus, available potassium and organic matter content in the crust under Calligonum mongolicum can explain 78.5 % of the change of its thickness.